TI_GERICHTE 12.2018.9 vom 20. April 2018 , Azione creditoria - tutela giurisdizionale nei casi manifesti - ripetibili - TI Tribunale d'appello (2018)
Azione creditoria - tutela giurisdizionale nei casi manifesti - ripetibili